Career Anxiety, Behavioral Intention, and Job-Seeking Behavior among Economics Students in Hanoi, Vietnam: A PLS-SEM Approach - Tran Ngoc Linh Nguyen; Vi Thi Ngoc Linh; Bui Huong Giang; Nguyen Hien Thao; Ngo Dieu Vy; Thi Lien Nguyen; Huy Hoang Doan (Lembaga Riset dan Inovasi Masyarakat Madani, 2026)
In an increasingly competitive labor market, employment has become a major concern for university students, particularly those in economics-related fields. According to the General Statistics Office, the unemployment rate among youth aged 15–24 reached 7.96% in 2024, highlighting growing challenges for young individuals entering the workforce. Additionally, a survey by the International School - Vietnam National University, Hanoi, reported that 41% of graduates work outside their fields of study, reflecting unclear career orientation and uncertainty in job choices. These pressures are further intensified by the rapid development of artificial intelligence (AI), which increases career-related uncertainty among economics students in Hanoi. This study aims to examine the impact of career anxiety on job search behavior, with behavioral intention serving as a mediating variable. A quantitative approach was employed using data collected from 174 economics students in Hanoi. The proposed relationships were tested using Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS. The results show that career anxiety does not directly affect job search behavior but influences it indirectly through the formation of behavioral intention. Career anxiety acts as a psychological signal that encourages students to plan and develop intentions to engage in job search activities. These findings suggest that career anxiety can serve as a motivating factor, promoting proactive career preparation. The study provides implications for universities and career support services in facilitating students’ transition from education to the labor market.